ECDIS Regulations in the Real World - Aalst, Joost van (The International Hydrographic Review, 2001)
During SASMEX 2000 at Brighton on 11 May 2000, the ECDIS Implementation Committee (ECIC) presented at a mock trial on the use of electronic charts. This session took place on the last conference day, and therefore got only limited attention. Nevertheless some very interesting views were presented on the practical implications of the present ECDIS Regulations. It is worthwhile making them available to a broader public.